PENGUATAN EKONOMI KELUARGA MELALUI SUBSISTENSI PRODUKSI - Mulyanti, Kurniawati; Hastuti, Isti Puji; Berry, Yunike (DEVOSI, 2022)
Strengthening the family economy through subsistence production is an important activity during the COVID-19 pandemic. Savings in expenditure by producing the goods needed by themselves, helps maintain family economic stability which in turn has an impact on the stability of family welfare. The program to strengthen the family economy through subsistence production aims to help housewives in an effort to save household expenses productively. The method applied in the socialization of this program is done with lectures and practice in the form of videos uploaded through the Watshaap group. Participants in this program are 52 housewives in Pedurenan Village, Mustika Jaya, Bekasi City. The enthusiasm of the program participants was supported by the cooperation of the village apparatus, especially the Lurah woman and the head of the PKK of the Pedurenan village, Mustikajaya